Strategi Inovatif Guru dalam Meningkatkan Pemahaman Siswa melalui Pembelajaran Berbasis Proyek (PjBL) pada Mata Pelajaran IPS di SD Negeri 1 Cilangkap - Daryanti, Daryanti; Ningsih, Tutuk (ANWARUL, 2025)
This study is motivated by social studies learning which is very important in education, but is often hampered by low student interest. This study aims to investigate teachers' innovative strategies in improving students' understanding of Social Studies learning at SD Negeri 1 Cilangkap, given the challenges of low interest and lack of innovation in learning. The research method used a descriptive qualitative approach through observation, interviews, and documentation. Data analysis includes reduction, presentation, and conclusion drawing. The results showed that the implementation of Project-Based Learning (PjBL) model increased students' engagement, enthusiasm, and understanding of social studies materials. PjBL also fosters students' social skills such as collaboration, communication, and problem solving. The conclusion of this research is that the innovative strategy of using the Project-Based Learning (PjBL) model improves students' understanding and shapes students' characters into competent and responsible individuals. The teacher acts as a facilitator, guiding students independently. The findings of this study contribute to the advancement of education in Indonesia, particularly improving the quality of social studies teaching in primary schools.